Wasps of the family Scoliidae (Hymenoptera, Aculeata) of NNP “Dvorichanskyi” - Kletenkin, V. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
When studying the biological diversity of the fauna of any territory and, in particular, the territory of a national nature park as a protected area, first of all, it is necessary to conduct an inventory of its individual components, as well as to prepare and publish summary reports. One of the important components of the entomofauna of any biotope or geographic region is Aculeata. When designing and creating the national nature park “Dvorichanskyi”, this group was not studied at all. Systematic studies of Aculeata were started by us in 2015. Traditional entomological methods of individual capture and Mörike traps were used for the studies. Studies were conducted on sandy wastelands with sparse vegetation, edges of pine and deciduous forests on the river Oskil terrace, steppe areas of limestone slopes, and in human settlements. The purpose of the study was an inventory of the family Scoliidae in the specified area. In general, 10 species of Scoliidae are known for Ukraine, and 9 for its continental part. The publication presents the results of our field studies on the territory of the national nature park “Dvorichanskyi” in 2015–2018 as an annotated list of six species of Scoliidae (Colpa (Colpa) sexmaculata (Fabricius, 1781), Colpa (Heterelis) quinquecincta (Fabricius, 1793), Megascolia (Regiscolia) maculata (Drury, 1773), Scolia (Discolia) hirta (Schrank, 1781), Scolia (Scolia) galbula (Pallas, 1771), Scolia (Scolia) sexmaculata (O.F.Müller, 1766)) from three genera (Colpa Dufour, 1841; Megascolia Betrem, 1928; Scolia Fabricius, 1775). One species, Megascolia maculata, is listed in the Red Book of Ukraine (2009) with the status “non-evaluated”. The list contains geographical data of research sites, information on biotope, and preliminary information on species abundance. The list is based on the author’s own specimens and observations. Literature sources and collections of the Museum of Nature of the Vasyl Karazin Kharkiv National University were studied. A brief history of studies of the modern territory of Kharkov region by scientists of the XIX century P.V.Ivanov, N.F.Beletsky, and V.A.Yaroshevsky is outlined.